Table of Content - - (Journal of engineering sciences and information technology, 2023)
Table of Content: 1. Evaluating the policy of removal and resettlement for residents of unsafe slums in greater Cairo according to the principles of sustainable development. Case study of Asmarat neighborhood. Eng. Mohamed Sobhi Abdel Ghani Hassan, Prof. Mohamed Abdel-Baqy Ibrahim , Prof. Ghada Farouk Hassan , Prof. Marwa Aboul Fotouh Khalifa 2. Railways Projects Appraisal Using Reference Class Forecasting and Fuzzy Sets Theory Eng. Dana Marwan Al Sheikh, Dr. Jamal Yunus Omran , Dr. Mudar Ali Alaaraj 3. Measure Effectiveness of SMS Spam Detection Model Based on Machine Learning Techniques Eng. Ahmed Hamed Osman, Dr. Muhammad Badawi Al-Khalifa 4. Study the Effect of Electromagnetic Radiation towards Sustainable Healthy Buildings Lecturer Sara N. Elkabany 5. Energy efficiency of conventional air conditioning systems in light of climate change Eng. Fawaz Khaled Ghaith